Evaluasi Keterampilan Mengajar Mengadakan Variasi Mahasiswa PGSD Semester VI Pada Mata Kuliah Pembelajaran Mikro - Prasita Puspita Sari (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2021)
This study aims to determine the ability of teaching skills to carry out variations possessed by PGSD students in semester 6 of class B in the 2021 academic year in micro learning courses. To achieve the research objectives, the researcher carried out activities through three stages, namely the planning stage, implementation stage, and evaluation stage and used descriptive research methods. The first stage is planning, in the planning stage students make a Learning Implementation Plan (RPP) which they will use in micro learning. Next is the implementation stage, students teach using the lesson plans that have been made to the micro class. The last stage is evaluation, when students carry out teaching activities, other students provide their assessments with questionnaires. Based on the results of the overall data analysis obtained a percentage value of 61.12%. So, it can be concluded that all skill indicators are in the “good” category.